2021
DOI: 10.1016/j.ijcard.2021.06.047
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac imaging in ischemic stroke or transient ischemic attack of undetermined cause: Systematic review & meta-analysis

Abstract: Background: Patients with ischemic stroke or transient ischemic attack (TIA) of undetermined cause often undergo cardiac imaging in search of a cardioembolic source. As the choice of the most appropriate imaging approach is controversial and therapeutic implications have changed over time, we aimed to identify in patients with "cryptogenic stroke or TIA" the yield of transthoracic or transesophageal echocardiography (TTE or TEE) and cardiac computed tomography (CT). Methods and results: We performed a systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
(75 reference statements)
0
5
0
1
Order By: Relevance
“…Patients with ischemic stroke related to cardio-embolism have a poorer prognosis compared to other stroke subtypes, including higher mortality and increased risk of stroke recurrence 13 . Moreover, in patients with stroke of undetermined etiology, LAA thrombus has been described as the most prevalent among major cardioembolic sources 14 . This study aimed to determine the additional value of spectral reconstructions for the detection of cardio-embolic sources in the setting of a one-stop shop stroke CT protocol including delayed-phase spectral cardiac CT-imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with ischemic stroke related to cardio-embolism have a poorer prognosis compared to other stroke subtypes, including higher mortality and increased risk of stroke recurrence 13 . Moreover, in patients with stroke of undetermined etiology, LAA thrombus has been described as the most prevalent among major cardioembolic sources 14 . This study aimed to determine the additional value of spectral reconstructions for the detection of cardio-embolic sources in the setting of a one-stop shop stroke CT protocol including delayed-phase spectral cardiac CT-imaging.…”
Section: Discussionmentioning
confidence: 99%
“…First, we compared cardiac CT with TTE rather than TEE, which has a higher diagnostic yield than TTE. 9,10 We used TTE because it is the recommended first-line screening method for the detection of structural sources of cardioembolism according to the Dutch and European guidelines 2,3 and is part of the stroke workup before classification as ESUS. 1 A large survey among neurologists also found that TEE is infrequently performed in patients with ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…8 The diagnostic yield of TTE for the detection of high-risk sources of embolism is limited with a yield of 1% for major sources of embolism in patients with cryptogenic stroke. 9 Transoesophageal echocardiography (TEE) has a higher diagnostic accuracy than TTE but is infrequently performed because it is invasive, may require sedation, and carries a small risk of complications 8,10…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Với 51 bệnh nhân trong nghiên cứu của chúng tôi được siêu âm qua thành ngực thì có 1 bệnh nhân phát hiện huyết khối thất trái với kích thước rất lớn 18mm chiếm 1,96% (Nghiên cứu của Gerlinde van der Maten là 0,97%, theo Margaret Morres là 1,94%). 5 Kết quả của chúng tôi khá tương đồng so với những nghiên cứu này. Tuy nhiên, với các nghiên cứu của nước ngoài, 1 số lượng bệnh nhân nhất định sẽ được tiến hành siêu âm tim qua thực quản để đánh giá khi có nghi ngờ và một tỷ lệ tương đối huyết khối buồng tim đã được phát hiện (Muhammad K Ahmed là 4,4%, theo Gerlinde van der Maten lên tới 18,04% theo Liqun Zhang năm 2012 là 6,67%).…”
Section: Bàn Luậnunclassified